Microbial water quality monitoring of raw and treated water sources in Harare and the effect of gender in disaster management due to water related disasters - Chirenda, Tatenda Grace (Rhodes University, Faculty of Pharmacy, Pharmacy, 2017)
Background - Microbial water quality monitoring is essential to the provision of potable water for domestic use. Unsafe water sources increase the risk of waterborne diseases. There is a need to raise awareness of legislature that supports management of water related disasters. Gender, education, health, and economic vulnerability contribute to the success of disaster management. Aim - This study aimed to investigate the microbial water quality of treated water in the Harare area. The study also researched the microbial water quality monitoring practices in Zimbabwe and how these contribute to the management of water borne diseases. The impact of gender, marriage, education, and disease in disaster management practices in Zimbabwe and South Africa was analysed. Method - Literature review was conducted on microbial water quality monitoring practices in Zimbabwe and legislature that supports disaster management. Practices of disaster management in Zimbabwe, and South Africa were investigated and compared. The perspective of the Harare community on the quality of their potable water was investigated through the use of a questionnaire and water quality testing was conducted using hydrogen sulphide test and R2A based heterotrophic plate count. Raw water supplying Manyame River and tap water in Harare households were assessed for microbial quality. Results and Discussion - Raw water sources were found to be contaminated by faecal matter. Household water sources had no faecal contamination, but tested positive for heterotrophic bacteria. The CFU/ml quantities obtained ranged from 1- 452 CFU/ml for all samples. The WHO guidelines for domestic water sources recommend that domestic water should have no coliforms/100 ml sample. Disaster management protocols were available in disaster prone areas such as the Matabeleland South Province. No guidelines were in place for monitoring microbial water quality as a disaster prevention method. Conclusion - The current state of treated water supplied by the Morton Jaffray Treatment Plant was found to be suitable for domestic use, but not sufficient to meet the Harare population's needs. The need to push for legislature supporting microbial water quality monitoring was recognised. Initiating public / private partnerships in water distribution and water quality monitoring in Zimbabwe was encouraged.
Keywords: Drinking water; Microbiology -- Zimbabwe -- Harare; Heterotrophic bacteria -- Zimbabwe -- Harare; Emergency management -- Zimbabwe -- Harare; Disasters -- Social aspects -- Zimbabwe -- Harare; Water quality management -- Zimbabwe -- Harare; Public health -- Zimbabwe -- Harare; Sex role -- Zimbabwe -- Harare